2013
DOI: 10.1128/iai.00822-12
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Francisella tularensis Schu S4 iglI , iglJ , and pdpC Genes Results in Attenuation for Growth in Human Macrophages and In Vivo Virulence in Mice and Reveals a Unique Phenotype for pdpC

Abstract: e Francisella tularensis is a facultative intracellular bacterial pathogen and the causative agent of tularemia. After infection of macrophages, the organism escapes from its phagosome and replicates to high density in the cytosol, but the bacterial factors required for these aspects of virulence are incompletely defined. Here, we describe the isolation and characterization of Francisella tularensis subsp. tularensis strain Schu S4 mutants that lack functional iglI, iglJ, or pdpC, three genes of the Francisell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
55
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 47 publications
(90 reference statements)
8
55
2
Order By: Relevance
“…Consistent with this result, Long et al found that while Schu S4 iglI and IglJ were essential for phagosomal escape and alteration of endosomal trafficking, a mutant lacking pdpC was only partially defective in this regard (30). This led to the conclusion that PdpC contributes to, but is not essential for, remodeling of the host phagosomal pathway (30). A similar result was reported for an LVS pdpC mutant (57).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Consistent with this result, Long et al found that while Schu S4 iglI and IglJ were essential for phagosomal escape and alteration of endosomal trafficking, a mutant lacking pdpC was only partially defective in this regard (30). This led to the conclusion that PdpC contributes to, but is not essential for, remodeling of the host phagosomal pathway (30). A similar result was reported for an LVS pdpC mutant (57).…”
Section: Discussionsupporting
confidence: 68%
“…Differences in intracellular replication and induction of host cell death pathways were also observed following infection of J774 macrophages with pdpC, iglC, iglG, or iglI mutants of LVS (56). Consistent with this result, Long et al found that while Schu S4 iglI and IglJ were essential for phagosomal escape and alteration of endosomal trafficking, a mutant lacking pdpC was only partially defective in this regard (30). This led to the conclusion that PdpC contributes to, but is not essential for, remodeling of the host phagosomal pathway (30).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations